Innovative Moments in Humanistic Therapy II: Analysis of Change Processes Across the Course of Three Cases of Grief Therapy. Issue 3 (2nd July 2016) - Piazza-Bonin, Elizabeth; Neimeyer, Robert A.; Alves, Daniela; Smigelsky, Melissa
Abstract : The current study is an extension of a complementary investigation examining links between process and outcome within six-session psychotherapies in which three eminent psychotherapists each worked with a bereaved client, using person-centered, existential, and constructivist approaches, respectively. The Innovative Moments Coding System (IMCS) was used in both studies to examine processes of change in the moment-by-moment unfolding of grief therapy. The initial study's findings help inform theory regarding the relevance of humanistic interventions when working with bereaved clients, particularly those that help promote meaning making in the wake of loss. The current investigation extends the original by offering a fine-grained analysis of the progression of innovative moments (IMs) in the context of good-outcome grief therapy, liking specific therapy procedures with positive indicators of client functioning, while providing case illustrations of each therapy dyad. Findings highlight the promise of humanistic approaches in grief therapy, and suggest directions for further research in this area. Implications for future use of the IMCS in psychotherapy process and outcome research are also discussed.